The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1071/bi9780247
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Concentrations in Ovine Plasma During its Intravenous Infusion, its Relation to the Production of Some Endogenous Hormones, and Some of the Effects on Wool Growth

Abstract: Plasma concentrations of dexamethasone have been measured in sheep during an 8-day infusion of dexamethasone-21-phosphate. The dexamethasone concentration profiles generally revealed a reproducible pattern with three phases-a peak during the first 48 h infusion which was followed by falling concentrations during the next 5 days, and a small increase in dexamethasone concentration during the final 24 h infusion was not uncommon. The pattern of dexamethasone concentrations was retained when dosage was arranged i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
2
1

Year Published

1978
1978
2002
2002

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 15 publications
2
16
2
1
Order By: Relevance
“…The concentration profiles for dexamethasone here were similar to those of Panaretto and Wallace (1978b). Leish and Panaretto (1978) reported similar concentration patterns using [3H]dexamethasone.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The concentration profiles for dexamethasone here were similar to those of Panaretto and Wallace (1978b). Leish and Panaretto (1978) reported similar concentration patterns using [3H]dexamethasone.…”
Section: Discussionsupporting
confidence: 69%
“…The peaks in steroid concentration have not been investigated here. The possibilities that exist to explain the initial peaks have been discussed by Panaretto and Wallace (1978b). The secondary peaks observed during the final 48 h infusion might represent rises in unconjugated steroid particularly in the older sheep used.…”
Section: Discussionmentioning
confidence: 99%
“…This approximated the dose, 8·5 mg kg-o. ?S, which was reported to cause the shedding of the whole fleece in the majority of sheep so treated (Panaretto and Wallace 1978a).…”
Section: The Sheep Their Housing and Nutritionmentioning
confidence: 99%
“…In animals infused intravenously with dexamethasone over a period of 8 days, Panaretto and Wallace (1978a) reported reproducible plasma concentration profiles with a peak during the first 48 h of infusion followed by falling levels with a small increase during the final days of infusion. Subsequently it has been found that the slow intravenous infusion of glucocorticoid analogues over an 8-day period caused wool shedding in a greater proportion of the total fibres than when the same dose was infused over a shorter period (Panaretto and Wallace 1978b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation